Bugis Language Interference with the Use of Indonesian Language in Communicating Students at SMP Negeri 1 Pammana - Sri Wahyuni; Ahmad Ghazali Samad (Journal of Indonesian Language Education and Literary, 2019)
This research based on the processes that language learning must be carried out following the rules. The school which is a place of formal education in educating students to use Indonesian language is good and right, in the form of written and oral terms. However, in reality, the problem of Indonesian conversion is still often found in schools, at various levels starting from the higher level, which is the cause of language acquisition and mastery of more than one language (bilingual). This can be done error which is usually called interference. Interference in language is usually called "language disease" because it can damage language so it must be avoided. This interference is a result of mixing a second language rules that are mastered by someone. The purpose of this research is to describe the form of Bugis language interference with the use of Indonesian used by junior high school students in Pammana sub-district in conversation and explain the translation of Bugis language interference on the ability to support junior high school students in Pammana sub-district. The method used in this research is descriptive qualitative method. The techniques of collecting data in this research are, conducting direct dialogue with students, inviting students to communicate well in the learning process. SMP Negeri 1 Pammana to interrupt Bugis language compilation to communicate or speak in Indonesian, this is done during formal conversations, this helps deviate from the rules of the Indonesian language.